Digitale d'autore Macchine, archivi e letterature - CARBE', EMMANUELA (Studi di letterature moderne e comparate, 2023)
The book starts with an introductory exploration on how writers use computers; gives a definition of Born-digital Literary Archives, provides a few examples from the international panorama and carries out a mapping of digital archives in Italy with a particular focus on Franco Fortini's Archive held at the University of Siena. The volume offers a summary of the first Italian project devoted to the Italian born-digital literary archives, PAD - Pavia Digital Archives, by analysing the process of acquisition and management of the materials, now kept at the Centro Manoscritti in Pavia. Finally a critical analysis of Francesco Pecoraro's first three works is offered through an examination of his digital archive in Pavia.